Decreased Functional Connectivity Between the Left Amygdala and Frontal Regions Interferes With Reading, Emotional, and Executive Functions in Children With Reading Difficulties - Nachshon, Ohad; Farah, Rola; Horowitz-Kraus, Tzipi (Frontiers in Human Neuroscience, 2020)
Introduction: Dyslexia is a reading disorder characterized by a significant difficulty in reading. Children with reading difficulties (RD) experience a broad range of social and emotional problems. Recently it was suggested that children with RD have altered functional connections within the amygdala, which is related to emotional processing. Since altered laterality related to reading was previously reported in children with RD, we sought to determine the differences in functional connectivity between the right and left emotional network as related to emotional challenges and the other reported difficulties in reading and EF in children with RD. Methods: Sixty 8-12 year-old children, 30 children with RD and 30 age-matched typical readers, participated in the study. Reading, emotional, and EF abilities were assessed. Global efficiency of the emotional network was calculated and compared between the groups, and left vs right functional connectivity of the amygdala was conducted using the CONN toolbox. Functional connectivity measures were then associated with measures of reading, emotional, and EF abilities. Results: Children with RD showed significantly decreased emotional and EF abilities compared to typical readers. Neuroimaging results showed decreased global efficiency measures within the emotional network in children with RD, who also showed lower functional connectivity between the amygdala and the left and right frontal pole regions. Results also indicated increased functional connectivity of the right vs the left amygdala with left and right precentral and postcentral gyri regions, which were related to decreased reading, emotional, and EF abilities in both typical readers and children with RD. Conclusions: The positive relationship between EF and emotional abilities in children with RD strengthens the relationship between EF difficulties and emotional stress, which in turn may lower EF abilities (monitoring, inhibition, and attention) as well as decreased reading abilities. Neuroimaging data motional challenges in children with RD are associated with decreased functional connectivity of the left amygdala with pre/post central gyrus and cognitive-control regions. These findings suggest that although the right hemisphere is thought to be related to emotional stress, it was the decreased control of the left hemisphere that was related to emotional disturbance in children with RD.